Private Biometrics Realisation Through Iris Verification - Chong, Siew Chin (2005)
Although biometrics is a powerful tool against repudiation, it still suffers from some inherent biometric specific threats. There is risk of being compromised by attacker where an attacker might use the biometrics information to masquerade as the person. The worst is a biometric feature cannot be replaced once it is compromised. In this research, we introduce the concept of private biometrics to overcome these drawbacks.